Robotic Pectoral Fin Thrust Vectoring Using Weighted Gait Combinations - John S. Palmisano; Jason D. Geder; Ravi Ramamurti; William C. Sandberg; Banahalli Ratna (Applied Bionics and Biomechanics)
A method was devised to vector propulsion of a robotic pectoral fin by means of actively controlling fin surface curvature. Separate flapping fin gaits were designed to maximize thrust for each of three different thrust vectors: forward, reverse, and lift. By using weighted combinations of these three pre-determined main gaits, new intermediate hybrid gaits for any desired propulsion vector can be created with smooth transitioning between these gaits. This weighted gait combination (WGC) method is applicable to other difficult-to-model actuators. Both 3D unsteady computational fluid dynamics (CFD) and experimental results are presented.